Turkey : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in Turkey during 1992-95. Economic activity expanded sharply in 1993, sustained by buoyant domestic demand that was underpinned by expansionary fiscal and monetary policies, but accompanied by a large deterioration in the current account position. The unsustainability of this policy stance resulted in an exchange and financial market crisis in the first months of 1994. In April 1994, the authorities announced a comprehensive stabilization program that included substantial fiscal retrenchment, monetary tightening, and a structural reform agenda intended to strengthen the adjustment effort over the medium term.